Efektivitas Model Pendidikan Olahraga terhadap Hasil Belajar Bola Voli Siswa Kelas Delapan - Afrizen Afrizen; Muhamad Sazeli Rifki; Alnedral Alnedral; Yuni Astuti (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study was conducted to determine whether the Sport Education Model can improve volleyball learning outcomes among eighth-grade students. In many physical education classes, instruction still relies heavily on teacher-centered approaches, which often limit students’ active involvement. As a result, students may have fewer opportunities to develop both their skills and motivation. Materials and methods. This study used a quasi-experimental design with a pretest–posttest control group setup. A total of 64 students from SMP Negeri 32 Padang participated in the research, with 32 students assigned to the experimental group and the remaining 32 placed in the control group. The study followed three main stages: pretest, treatment, and posttest. At the beginning, both groups were given a pretest to measure their initial abilities in cognitive, psychomotor, and affective domains. The experimental group then received instruction through the Sport Education Model, which emphasizes teamwork, student roles, and game-based activities. The control group received traditional instruction that mainly relied on explanations and repetitive practice. After the treatment period, both groups were given a posttest. The collected data were then analyzed using descriptive statistics and an independent samples t-test. Results. The findings revealed that the experimental group showed greater progress compared to the control group. Improvements were seen in understanding, skill performance, and participation. Statistical testing confirmed that the difference between the two groups was significant. Conclusion. The Sport Education Model proved effective in enhancing volleyball learning outcomes. Approaches that encourage active participation and teamwork appear to provide better learning experiences and outcomes for students.